ASSOCIATION OF NOVEL POLYMORPHISM OF ESR2 GENE (G40100A) WITH PRODUCTION TRAITS OF BROWN LOCAL IRAQI CHICKEN - Abu-Rekaiba, R.. I. A.; Razuki, W. M.; AL-Anbari, E. H. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The estrogen receptor 2 (ESR2) plays a crucial role in the growth and development of follicles and ovulation in chickens. The aim of this study was detect the association of estrogen receptor 2(ESR2) gene polymorphisms with the production performance of brown local Iraqi chicken. A total of 104 hens from the F4th generation of local chicken selected for high egg yield were used. The novel SNP(G40100A) transition within third prime untranslated region (3 prime UTR) of ESR2 gene. Three genotypes were found: Wild(GG), Heterozygous(GA), and Homozygous(AA) through (PCR-DAN sequencing). Chi-square analysis showed no significant in genotypic and allelic frequencies for SNP which were agreement with Hardy-Weinberg equilibrium. The genotypes GG and GA were significantly superior with age at sexual maturity compared to AA genotype. The genotype GA was significantly associated with hen day egg production (HDEP) at 30 weeks compared to genotype AA, as well as the genotype GA highest significant variance was reported comparing with the GG genotype in HDEP at 45 and 60 weeks, thus, the study recommends to exploit this ESR2 gene polymorphism (G40100A) as promising marker in breeding program via, the selection of individuals carrying the genotype GA, characterized by the high egg production.